2010
DOI: 10.1007/s12160-010-9242-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Causal Information on Medical Students’ Clinical Encounters with an Obese Virtual Patient: Health Promotion and Social Stigma

Abstract: Background-Health care providers will increasingly encounter information about the genetics of obesity as genetics research progresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 51 publications
2
50
1
2
Order By: Relevance
“…individuals not selected for being overweight or obese) using genetic information have shown inconsistent results [22,[27][28][29][30][31] . In an innovative study using virtual reality, medical students who interacted with an obese virtual patient after reading information about genetic mechanisms in obesity exhibited significantly less negative stereotyping of the patient than a control group who did not read genetic information [32] . In related research, the results of a randomized controlled trial indicated that obese individuals with a family history of obesity who were provided with personalized genetic information about obesity showed reductions in self-blame [33] .…”
Section: Genomics and Internalized Weight Stigmamentioning
confidence: 99%
“…individuals not selected for being overweight or obese) using genetic information have shown inconsistent results [22,[27][28][29][30][31] . In an innovative study using virtual reality, medical students who interacted with an obese virtual patient after reading information about genetic mechanisms in obesity exhibited significantly less negative stereotyping of the patient than a control group who did not read genetic information [32] . In related research, the results of a randomized controlled trial indicated that obese individuals with a family history of obesity who were provided with personalized genetic information about obesity showed reductions in self-blame [33] .…”
Section: Genomics and Internalized Weight Stigmamentioning
confidence: 99%
“…Accordingly, they demonstrate stereotypical attitudes towards obese patients connoting poor self-control and lack of willpower, being sloppy, less likely to adhere to treatment, unsuccessful and responsible for their symptoms (Persky & Eccleston, 2011;Swift et al, 2013a;Wigton & McGaghie, 2001). Use of derogatory remarks on obese persons by medical students has also been reported (Wear et al, 2006).…”
Section: Attitudes Of Healthcare Staff Promoting Weight-biasmentioning
confidence: 99%
“…From the providers' perspective, medical students indicate less negative stereotyping of overweight patients if they read about genetic mechanisms of obesity, compared to reading about behavioral mechanisms (Persky & Eccleston, 2011). From the patients' perspective, provision of genomic information in a primary care context can reduce patients' perceived stigma because they feel less blamed for their weight (Persky & Street, 2015).…”
Section: Integrating Genomic Information To Reduce Perceived Blame Anmentioning
confidence: 99%